ANALYSIS OF THE IMPLEMENTATION OF ORGANIZATIONAL COMMITMENT TOWARDS JOB SATISFACTION WHICH IMPLICATIONS EMPLOYEE PERFORMANCE (SURVEY STUDY AT HERMANA LEMBEAN MANADO HOSPITAL) - Mogi, Melati Rosaline Michaella; Yuliaty, Farida; Rasyid, Renaldi Prasetya Nagar; Kosasih, Kosasih; Nugroho, Taufan (HEARTY, 2026)
Organizational commitment is part of an effort or initiative from within an individual to the maximum to survive, work hard, and have confidence in the goals of the organization. Employees as human resources who contribute to health services in hospitals. Therefore, employees contribute to determining the quality of services in hospitals. This study aims to analyze the implementation of organizational commitment, job satisfaction and employee performance at Hermana Lembean Hospital, Manado. This study uses a quantitative approach. The sample in this study amounted to 72 respondents. Data analysis used is descriptive analysis and verification analysis using path analysis. The results of the descriptive analysis study on the implementation of organizational commitment, job satisfaction and employee performance of respondents gave a good assessment, there were still some shortcomings that must be considered for improvement. While the results of the verification study, the path analysis model showed that the path coefficient value between variables was positive and the indirect influence path coefficient value was greater than the direct influence (53.7%> 65.6%), meaning that the job satisfaction variable as an intervening variable was able to mediate the implementation variable of organizational commitment with employee performance variables.